2020
DOI: 10.3390/nu12113301
|View full text |Cite
|
Sign up to set email alerts
|

ω-3 Polyunsaturated Fatty Acids on Colonic Inflammation and Colon Cancer: Roles of Lipid-Metabolizing Enzymes Involved

Abstract: Substantial human and animal studies support the beneficial effects of ω-3 polyunsaturated fatty acids (PUFAs) on colonic inflammation and colorectal cancer (CRC). However, there are inconsistent results, which have shown that ω-3 PUFAs have no effect or even detrimental effects, making it difficult to effectively implement ω-3 PUFAs for disease prevention. A better understanding of the molecular mechanisms for the anti-inflammatory and anticancer effects of ω-3 PUFAs will help to clarify their potential healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 125 publications
(184 reference statements)
0
15
0
Order By: Relevance
“…For eicosanoids and related mediators, the signals of AA derivatives might be theoretically enhanced, which are especially concordant with the established roles of PGE2 pathway in the pathogenesis of colon cancer 1,2 . On the contrary, increased levels of EPA and DHA metabolites might serve as anti‐cancer properties 8 . Considering their protective roles in inflammation, these modulations might be compensatory changes provoked against cancer cells in the mice.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…For eicosanoids and related mediators, the signals of AA derivatives might be theoretically enhanced, which are especially concordant with the established roles of PGE2 pathway in the pathogenesis of colon cancer 1,2 . On the contrary, increased levels of EPA and DHA metabolites might serve as anti‐cancer properties 8 . Considering their protective roles in inflammation, these modulations might be compensatory changes provoked against cancer cells in the mice.…”
Section: Discussionmentioning
confidence: 56%
“…Both basic and clinical studies have shown that inhibition of PGE2 production by COX inhibitors suppresses colon cancer 3,4 . Dietary EPA and DHA supplementation has been demonstrated to suppress cancer in human subjects 5–7 and the metabolites derived from these ω3 fatty acids have been demonstrated to exhibit anti‐cancer activity through suppression of inflammation and/or the induction of apoptosis 8 …”
Section: Introductionmentioning
confidence: 99%
“…Other numerous epidemiological and preclinical studies further support the preventive effects of ω-3 PUFA on CRC. For example, in the VITamins And Lifestyle (VITAL) cohort study, subjects who routinely took fish oil supplements had lower risks of developing CRC than those who didn't take supplements (53,54). Another study, carried out by the European Prospective Investigation into Cancer and Nutrition (EPIC) showed that increased consumption of ω-3 PUFA reduces the risks of CRC (55).…”
Section: ω-3 Pufas: Role In the Prevention Of Colorectal Cancermentioning
confidence: 99%
“…Omega-3 polyunsaturated fatty acids (omega-3-PUFAs) are generally recognized both as dietary supplements and prescription medications. Increasing data from epidemiologic, clinical, and preclinical investigations show that omega-3-PUFAs are effective in preventing CRC [ 10 ].…”
Section: Introductionmentioning
confidence: 99%